COOPERATIVE TEACHING LEARNING BERBASIS NUMBERED HEAD TOGETHER MENINGKATKAN PRESTASI BELAJAR SISWA KELAS 5 SDN KALINUSU 01 - M Rifaizin (JGuruku: Jurnal Penelitian Guru, 2023)
ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar Peserta Didik di kelas 5 SDN Kalinusu 01 melalui penerapan model pembelajaran kooperatif tipe NHT (Number Head Together). Data hasil belajar Peserta Didik yang terkumpul dianalisis secara kualitatif. Hasil penelitian ini menunjukkan bahwa penerapan model pembelajaran kooperatif tipe NHT (Number Head Together) dapat meningkatkan hasil belajar Peserta Didik kelas 5 SDN Kalinusu 01. Hal ini dapat dilihat dari peningkatan hasil belajar Peserta Didik pada siklus I nilai rata-rata Peserta Didik 71,8 dengan persentase ketuntasan belajar 65% dan nilai rata Peserta Didik pada siklus II 80 dengan persentase ketuntasan belajar 95%. Dengan demikian, terdapat peningkatan hasil belajar Peserta Didik setelah menerapkan model pembelajaran NHT (Number Head Together), sehingga dapat disimpulkan bahwa model pembelajaran NHT (Number Head Together) dapat meningkatkan hasil belajar Peserta Didik pada subtema 1 ciri-ciri makhluk hidup di kelas 5 SDN Kalinusu 01 Kabupaten Brebes. Kata kunci: Cooperative Teaching Learning, Numbered Head Together COOPERATIVE TEACHING LEARNING BASED ON NUMBERED HEAD TOGETHER IMPROVES LEARNING ACHIEVEMENT OF GRADE 5 STUDENTS OF SDN KALINUSU 01 ABSTRACT This study aims to improve the learning outcomes of students in grade 5 SDN Kalinusu 01 through the application of the NHT (Number Head Together) type cooperative learning model. The collected data on student learning outcomes are analyzed qualitatively. The results of this study show that the application of the NHT (Number Head Together) type cooperative learning model can improve the learning outcomes of grade 5 students of SDN Kalinusu 01. This can be seen from the increase in student learning outcomes in cycle I the average score of students is 71.8 with a percentage of learning completeness of 65% and the average value of students in cycle II is 80 with a percentage of learning completeness of 95%. Thus, there is an increase in student learning outcomes after applying the NHT (Number Head Together) learning model, so it can be concluded that the NHT (Number Head Together) learning model can improve student learning outcomes in subtheme 1 characteristics of living things in grade 5 SDN Kalinusu 01 Brebes Regency. Keywords: Cooperative Teaching Learning, Numbered Head Together